PRELIMINARY STUDY ON 4 YEAR OLD HOPEA ODORATA VEGETATIVE PROPAGATION - Kajornsrichon, Sunanta (วารสารวนศาสตร์ไทย, 2022)
Rooting potential of lateral branch cuttings of 4 year-old-Hopea odorata, and effect of hedge height on shoot production of saplings were studied. It was found that rooting potential of branch cuttings differed significantly among ortets and positions on branches, but not among positions on stem. The average rooting percentage was 7.23. The maximum rooting percentage was 27.22, while the minimum was nil. In the hedging experiment, hedge height and diameter at root collar of saplings significantly affected shoot production. Hedge height at 20 - 30 cm was recommended, whereas hedging at 20 cm height induced the maximum shoots (8.98 shoots/sapling). Hedging at every level induced orthotropic shoots. The average number of shoots produced from saplings in the 30 - 40 mm diameter class showed the best production (8.83 shoots/sapling).